INTЕGRАTIVЕ MЕTHОDS АND MЕАNS ОF TЕАCHING THЕ SPЕCIАL PЕDАGОGICАL MОDULЕ - Khаkkulоv Kоmil Yusupоvich (Modern American Journals, 2025)
Physics occupies a special place among natural sciences, so it is said that it forms the foundation of all natural sciences. Because physics has made and continues to contribute to the achievements of all natural sciences. Examples of this are physical chemistry, chemical physics, biophysics, astrophysics, geophysics and other sciences.
Keywords: directive, goal, concepts, international, matter, complex, methodological, polytechnic, scientific evidence, methodology of teaching topics, general-theoretical issues.